Bor'ba obščestvennych sil v russkoj revoljucii v 1905 i 1906 gg. ("Dviženie")
Vl. Gorn ps. Vladimira Gustavoviča Gromana V. Meč ps. Vladimira Dmitrieviča Mačinskago. - Čerevanin ps. Fedora Andreeviča Lipkina. 1: Sily reakcii / V. Meč. - 1907. - 100 p